Students’ Perception on Writing Problems: A Survey at One Islamic University in Jambi - Akhmad Habibi; Sri Wachyunni; Nur Husni (Ta'dib: Jurnal Pendidikan Islam, 2017)
The aim of this research was to find out students' problems in writing in the fifth-semester students in one Islamic University in Jambi. We used survey and the population of this research was the fifth-semester students consisting of 198 students. 70 students were selected as the sample. The questionnaire consists of 28 questions of 7 types of problems with 5 alternative answers. The researcher used SPSS to analyze the data. It was found that there were 7 types of the problems that students faced in their writing course. They were poor organization/illogical sequence, problems of word choice, grammatical error, spelling problems, supporting ideas confusions, punctuation problems, and capitalization. The overall mean of students' problems in writing in the fifth-semester students in Islamic Institution in Jambi was (x=2.70) categorized as "medium". Specifically, students problems in poor organization/illogical sequence was (x=3.69) , problem of word choice (x=3.72), grammatical error (x=3.25), spelling problem (x=3.35), confused on supporting the ideas (x=3.12), punctuation problem (x=3.17), capitalization (x=3.35). All the process in scientific approach was categorized as "medium" for the students. It means that the students did not find significant difficulty in writing course. Moreover, from the interpretation of the mean, and most of the students agreed that they had  dominant problems; word choice and poor organization/illogical sequence.